A micromechanics method for transverse creep behavior induced by interface diffusion in unidirectional fiber-reinforced metal matrix composites. (1st March 2019) - Xu, Binbin; Guo, Fenglin
Highlights: Propose a new micromechanics method to analyze creep behavior induced by interface diffusion in metal matrix composites. Present an analytical solution for creep rate due to interfacial diffusion. Formulate a micromechanics model to estimate the stress field in the fiber accounting for interaction between fibers. Obtain overall creep strains and stress variation with time in fibers under constant external load by the incremental creep analysis procedures. Abstract: In this study, we present a new micromechanics method to predict the transverse creep rate induced by interface diffusion in unidirectional fiber-reinforced composites and evolution of overall creep strain under constant applied stress. An analytical solution for creep rate induced by interfacial diffusion, depending on the applied stress, fiber volume fraction and radius of the fiber, as well as the modulus ratio between the fiber and the matrix, is obtained. A micromechanics model is proposed to estimate the stress field in the fiber, which is related to the driving force for the interface diffusion, the normal stress on the interface. Comparison with finite element analysis shows that the present micromechanics model is of good accuracy, especially for high fiber volume fraction and large elastic modulus ratio between fiber and matrix. With the proposed micromechanics method based on the average field theory, the variation of overall creep strains and stresses with time in fibers under constant external load are analyzed by the incremental creep analysis procedures.